Effect of nanoparticle shapes on heat transfer characteristics and thermodynamic performance of a shell and tube heat exchanger / Miqdad Khairulmaini - Miqdad, Khairulmainif (2012)
The use of nanofluids as working fluids have resulted in increased performance for various applications involving heat transfer in today’s industrial sector. Many studies on nanofluids have been conducted for shell and tube heat exchanger performance based on spherical shaped nanoparticles. The objective of this research project is to study the effects of different nanoparticle shapes for nanofluids in terms of heat transfer characteristics (i.e. heat transfer coefficient, and overall transfer coefficient), and also determine the thermodynamic performance for a shell and tube heat exchanger used in a waste heat recovery industry (i.e. heat transfer rate, and entropy generation). The effect of four types of nanoparticle shapes were studied (i.e. platelets, blades, cylinders, and bricks) for this research project. The results showed an increase in both heat transfer characteristics and thermodynamic performance for all nanoparticle shapes when compared to conventional basefluid. From the results obtained, it was established that EG/H2O-AlOOH nanofluid containing cylinder shaped nanoparticles was the best performing nanofluid with an increase of 3.9% for heat transfer coefficient (h), 1.9% for overall heat transfer coefficient (Uo), and 1.3% for heat transfer rate (q). Although increase in entropy generation minimization for EG/H2OAlOOH nanofluid containing cylinder shaped nanoparticle was lowest (1.48%) compared to the remaining EG/H2O-AlOOH nanofluids containing the remaining nanoparticle shapes, the percentage difference was less 0.5%. Two comparison studies were conducted with respect to EG/H2O-AlOOH nanofluid containing the best performing nanoparticle shape. The first comparison study was between EG/H2OAlOOH nanofluid containing cylinder shaped nanoparticles and EG/H2O-AlOOH containing spherical shaped nanoparticles. While the second comparison study was between EG/H2O-AlOOH nanofluid containing cylinder shaped nanoparticles with and without considering the size factor of the nanoparticle shape. Comparison between EG/H2O-AlOOH nanofluid containing cylinder shaped nanoparticle and EG/H2OAlOOH nanofluid containing conventional shaped nanoparticle showed an increase in heat transfer characteristics (2.4% for heat transfer coefficient, h and 1.14% for overall heat transfer coefficient, Uo) and thermodynamic performance (0.88% for heat transfer rate, q) for the former nanofluid. While comparison between EG/H2O-AlOOH nanofluid containing cylinder shaped nanoparticles with and without considering the size factor, heat transfer characteristics and thermodynamic performance were slightly lower (0.88% for heat transfer coefficient, h, 0.40% for overall heat transfer coefficient, Uo, and 0.30% for heat transfer rate, q). The reason behind this was that if size factor was not taken into consideration, the thermal resistance between nanoparticles and basefluid was neglected, resulting in the increase in theoretical performance. Overall, this study clearly showed the effect of different nanoparticle shapes in terms of heat transfer characteristics and thermodynamic performance.